(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article provides a comprehensive assessment of macroeconomic factors affecting the number of private business entities operating in the Republic of Uzbekistan for 2010– 2024 using econometric methods. The main objective of the study is to determine the relationship between the number of private enterprises and tax incentives, electricity production rates, fixed capital investments, and the consumer price index using correlation-regression analysis and to develop a multifactor econometric model. The scientific novelty of the study lies in the assessment of the development of the private sector using complex econometric modeling based on several macroeconomic indicators at the same time. The practical significance of the results is manifested in the possibility of using them to improve the state’s fiscal and investment policy, optimize entrepreneurship support mechanisms, and develop long-term economic forecasts.